Probing the local nature of excitons and plasmons in few-layer MoS2 - Hannah Catherine Nerl (Nature Portfolio, 2017)
Probing excitons and plasmons at the nanoscale This paper outlines a template protocol to map the local nature of electronic excitations were they happen, at the nanoscale. An unprecedented combination of energy and spatial resolution (using monochromated low-loss scanning-transmission-electron-microscopy electron-energy-loss spectroscopy) was used to map for the first time local electronic excitations of 2D nanomaterials. These are crucially important to understand and explain any type of opto-electronic behaviour in 2D materials. Using this cutting-edge technique combined with a computational approach we were able to unravel the full set of electronic excitations (plasmonic and excitonic) in MoS2 nanosheets over a wide energy range. This study will be important for the application of nanomaterials for realistic applications in opto-electronics.